GAS CHROMATOGRAPHY-MASS SPECTROMETRY OF Murraya exotica ESSENTIAL OIL EXTRACTED THROUGH DIFFERENT EXTRACTION TECHNIQUES - M. K. Naseem; A. Younis; M. A. Khan; R. Ahmad (Journal of Animal and Plant Sciences, 2015)
The trial was conducted to explore the essential oil production potential of Murraya exotica under Faisalabad conditions through various extraction methods viz. solvent extraction, steam distillation, and supercritical fluid extraction (SCFE). SCFE was found to be the most efficient method for the extraction of good quality essential oil from M. exotica flowers. Gas chromatography-mass spectrometry (GC-MS) was performed for the characterization of chemical constituents contained in the essential oil of M. exotica. It was observed that 41 components representing 99.94% of the oil were identified from supercritical fluid extraction method (SCFE) while 46 and 49 components that constitute 96.4% and 88.7% of the oils were analyzed from solvent and steam distillation methods respectively. It was noted that manool, E-nerolidol, germacrene D, benzyl benzoate, palmitic acid, methyl palmitate δ-cadinene and anthranilic acid, were found as the major components in essential oil. The values of other physio-chemical parameters viz. refractive index, optical rotation, specific gravity, congealing point, acid and ester number were variable in oil extracted through different methods.
Keywords: physiochemical; solvent extraction; steam distillation; supercritical fluid extraction